Au@TiO2 Core–Shell Composites for the Photocatalytic Reduction of CO2. Issue 47 (27th June 2018) - Pougin, Anna; Dodekatos, Georgios; Dilla, Martin; Tüysüz, Harun; Strunk, Jennifer
Abstract: Au/TiO2 catalysts in different geometrical arrangements were designed to explore the role of morphology and structural properties for the photocatalytic reduction of CO2 with H2 O in the gas‐phase. The most active sample was a Au@TiO2 core–shell catalyst with additional Au nanoparticles (NPs) deposited on the outer surface of the TiO2 shell. CH4 and CO are the primary carbon‐containing products. Large amounts of H2 are additionally formed by photocatalytic H2 O splitting. Shell thickness plays a critical role. The highest yields were observed with the thickest layer of TiO2, stressing the importance of the semiconductor for the reaction. Commercial TiO2 with and without Au NPs was less active in the production of CH4 and CO. The enhanced activation of CO2 on the core–shell system is concluded to result from electronic interaction between the gold core, the titania shell, and the Au NPs on the outer surface. The improved exposure of Au−TiO2 interface contributes to the beneficial effect. Abstract : Wrapped up and decorated : With Au@TiO2 core–shell composites featuring additional Au nanoparticles on the outer surface, higher yields of CH4 and CO can be obtained in photocatalytic CO2 reduction. Large amounts of H2 from H2 O splitting are simultaneously produced. Electronic effects and the catalytic role of gold dominate the performance of the system.